Baseline FeNO as a prognostic biomarker for subsequent severe asthma exacerbations in patients with uncontrolled, moderate-to-severe asthma receiving placebo in the LIBERTY ASTHMA QUEST study: a post-hoc analysis. Issue 10 (October 2021) - Busse, William W; Wenzel, Sally E; Casale, Thomas B; FitzGerald, J Mark; Rice, Megan S; Daizadeh, Nadia; Deniz, Yamo; Patel, Naimish; Harel, Sivan; Rowe, Paul J; Graham, Neil M H; O'Riordan, Thomas; et al.
Summary: Background: Fractional exhaled nitric oxide (FeNO) has potential as a prognostic biomarker in asthma, but its prognostic value among other recognised indicators is unclear. We assessed the added prognostic value of baseline FeNO to blood eosinophil count and prior severe asthma exacerbations for subsequent exacerbations. Methods: In this post-hoc analysis of the 52-week, double-blind, phase 3 LIBERTY ASTHMA QUEST study, we identified 620 patients with moderate-to-severe asthma who were randomly assigned to placebo; had uncontrolled asthma with inhaled glucocorticoids plus up to two controllers; one or more exacerbations in the previous year; FEV1 percent predicted 40–80%; FEV1 reversibility of 12% or higher and 200 mL; Asthma Control Questionnaire (ACQ-5) score of 1·5 or higher; and complete data on baseline type 2 biomarkers (FeNO, eosinophils, and total IgE) with no baseline minimum requirement. Annualised severe exacerbation rate was assessed by baseline FeNO (<25 ppb, ≥25 to <50 ppb, ≥50 ppb; negative binomial model) and cross-classified by baseline blood eosinophils (<150 cells per μL, ≥150 to <300 cells per μL, ≥300 cells per μL) and prior exacerbations (one, two or more), all adjusted for baseline ACQ-5, postbronchodilator FEV1, and other clinical characteristics. Post-hoc analyses were done in the intention-to-treat population. The LIBERTY ASTHMA QUEST STUDY is registered on ClinicalTrials.gov, NCT02414854, and is complete. Findings: Patients with baseline FeNO of 50 ppb or higher (n=144) had a 1·54-times higher exacerbation rate than patients with FeNO of less than 25 ppb (n=291; relative risk 1·54 [95% CI 1·11–2·14]; p=0·0097). Patients with baseline FeNO of 25 to <50 ppb (n=185) had a 1·33-times higher exacerbation rate than patients with FeNO of less than 25 ppb (1·33 [0·99–1·78]; p=0·0572). Patients with baseline FeNO of 25 ppb or higher, a blood eosinophil count of 150 cells per μL or higher, and two or more prior exacerbations (n=157) had an exacerbation rate 3·62-times higher than patients with FeNO of less than 25 ppb, a blood eosinophil count of less than 150 cells per μL, and one prior exacerbation (n=116; 3·62 [1·67–7·81]; p=0·0011). Interpretation: In uncontrolled, moderate-to-severe asthma, higher baseline FeNO levels were associated with greater risk of severe asthma exacerbations, particularly in combination with elevated eosinophil count and prior exacerbations, supporting the added value of FeNO as a prognostic biomarker. Further research is needed to confirm FeNO as an independent predictor for asthma exacerbations. Funding: Sanofi and Regeneron Pharmaceuticals.